EFEKTIVITAS AKUN INSTAGRAM @jktinfo SEBAGAI MEDIA INFORMASI LALU LINTAS BAGI MASYARAKAT JAKARTA - Benedictus Dennis Bernard; Mutiara Pupa Aliya (Jurnal Komunikasi & Media Digital, 2025)
Information regarding traffic conditions is considered to be important nowadays, especially in populous areas like Greater Jakarta, where traffic jams often happen. Therefore, people rely on digital technology to obtain fast and immediate information. One of which was @jktinfo on Instagram. This research aimed to analyse the effectiveness of @jktinfo in distributing information about Jakarta’s traffic. This research utilised cognitive response models consisting of three dimensions: message content, source, and execution. This research used a quantitative approach with a survey method on 100 respondents between the ages of eighteen and thirty years old who had access to @jktinfo's content on Jakarta’s traffic. The research instrument was a questionnaire, which was analysed to disclose the effectiveness of @jktinfo in distributing information about Jakarta’s traffic. The research found that 51,75% of respondents really agreed that the content of the messages was clear and could be understood, 46% agree that the source is credible, whilst 61,80% of respondents really agreed that the use of carousel and caption feature were utilised well. The message execution dimension was the one that stood out. This showed that visual power, message interconnectedness, and the writing style played an important role in fulfilling the needs of traffic information.